A review of Coelopoetinae (Lepidoptera, Gelechioidea, Pterolonchidae), a moth subfamily confined to western North America, with descriptions of seven new species - Kaila, Lauri (Zootaxa, 2024)
Systematics and taxonomy of the gelechioid subfamily Coelopoetinae are reviewed. Following the current classification, this group is considered to form its own monotypic subfamily in Pterolonchidae with one recognized genus, Coelopoeta, after a convoluted and, in part, arguably conjectural, historical systematic treatment. On morphological basis (appearance, male genitalia) and with support from DNA barcodes, the genus is divided into two discrete units probably meriting recognition as separate genera. The species groups are informally treated as the nominate C. glutinosi species group, and the C. fissurina species group. In the absence of knowledge of females or the biologies of any of the species of the C. fissurina group, species of both groups are here provisionally included in Coelopoeta. In total, 10 species are recognized, seven of which are here described as new: C. glutinosi species group: C. alboflava Kaila, sp. nov., C. aprica Kaila, sp. nov., C. aurora Kaila, sp. nov., C. fulminea Kaila, sp. nov. and C. sariae Kaila, sp. nov.; C. fissurina species group: C. fissurina Kaila, sp. nov. and C. valalbui Kaila, sp. nov. The three previously known species, C. glutinosi Walsingham, 1907, C. maiadella Kaila, 1995 and C. phaceliae Kaila, 1995 are redescribed. All three of these species belong to the glutinosi species group. A lectotype is designated for C. glutinosi Walsingham, 1907. Some southwestern Coelopoeta species are potentially under threat of decline or even extinction due to the apparently increasingly intense and frequent forest fires. This threat is significant as the species with known life histories spend their entire life cycles above ground in low vegetation.